Related liver fragment transplantation for type 1 glycogenosis: the first Russian experience The paper describes two clinical examples of successful related liver fragment transplantation for type 1 glycogenosis in a one-year-old boy and a 6-year-old girl. The given first successful clinical experience suggests that liver fragments for type 1 glycogenoses can be transplanted from live related donors and offers promise for the radical treatment of patients with this pathology. - A. V. Filin; A. V. Semenkov; N. A. Koroteyeva; A. Ya. Keligova; A. V. Metelin; E. F. Kim; D. S. Dzhamanchin; N. E. Khartukova; Yu. R. Kamalov; E. Yu. Kryzhanovskaya; V. A. Khovrin; T. N. Galyan; et al. (Трансплантология (Москва))
The paper describes two clinical examples of successful related liver fragment transplantation for type 1 glycogenosis in a one-year-old boy and a 6-year-old girl. The given first successful clinical experience suggests that liver fragments for type 1 glycogenoses can be transplanted from live related donors and offers promise for the radical treatment of patients with this pathology.